Bahasa Inggris - Muharraran, Firdha; Tarigan, Susiani; Delfira, Rizqina (Postgraduate, University of Mataram, 2023)
Lactobacillus acidophilus one of the bacteria that causes caries among other Lactobacillus species. Mint leaves (Mentha piperita L.) contain active compounds as antibacterials. The aim of this research was to determine the effectiveness of mint leaf extract (Mentha piperita L.) mouthspray in concentrations of 5%, 10%, 25%, 50% against Lactobacillus acidophilus. Type of this research is true experimental with post test only control group design. The sample is pure culture of Lactobacillus acidophilus and 24 students Dentist Study Program, Prima Indonesia University. Antibacterial testing used the disc diffusion method and the solution was made with pure extract and distilled water. Organoleptic data was collected by questionnaire then analyzed using the Kruskal-Wallis and Mann-Whitney. The results is showed the majority of panelists stated did not like the color, aroma and taste of the mouthspray of mint leaf extract (Mentha piperita L.). In the antibacterial test, the inhibition zone was obtained with concentrations of 10%, 25%, 50% and positive control was 3.70 ± 4.273 mm; 8.88±1,250 mm; 11.33 ± 0.126 mm; 11.34 ± 0.126 mm, while the 5% and negative control had no obstacles. This research shows that mouthspray solution has a safe formula as an oral preparation and has antibacterial activity